2020
DOI: 10.1021/acsomega.0c02983
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mutations on the Conformational Transition from α-Helix to β-Sheet Structures in Arctic-Type Aβ40: Insights from Molecular Dynamics Simulations

Abstract: The amyloid-β (Aβ) protein aggregation into toxic oligomers and fibrils has been recognized as a key player in the pathogenesis of Alzheimer’s disease. Recent experiments reported that a double alanine mutation (L17A/F19A) in the central hydrophobic core (CHC) region of [G22]Aβ 40 (familial Arctic mutation) diminished the self-assembly propensity of [G22]Aβ 40 . However, the molecular mechanism behind the decreased aggregation tendency of [A17/A19/G22]Aβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Therefore, the Aβ peptide must undergo a conformational transition from α-helix to intramolecular β-sheet before aggregation. As the essential step for Aβ aggregation, this conformational transition has also been the focus of extensive studies in recent years [25] , [26] , [27] , [28] . The investigation of conformational transitions can be helpful in probing the initial stages of aggregation and providing valuable structural insights into the inhibition of aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Aβ peptide must undergo a conformational transition from α-helix to intramolecular β-sheet before aggregation. As the essential step for Aβ aggregation, this conformational transition has also been the focus of extensive studies in recent years [25] , [26] , [27] , [28] . The investigation of conformational transitions can be helpful in probing the initial stages of aggregation and providing valuable structural insights into the inhibition of aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the Ab peptide modify its toxicity, assembly, and rate of bril formation. Specically, the mutations in the CHC and loop regions, including F19W, 36 F20W, 36 L17A/F19A, 37 Flemish A21G, 38 Dutch E22Q, 39 Italian E22K, 40 Arctic E22G, 41,42 E22D, 43 and Iowa D23N 44 could affect the conformational changes in Ab oligomers. Another example shown that the combination of mutation A2V in N-terminal and histidine tautomerism can affect the Ab monomer structures and its aggregation process.…”
Section: Introductionmentioning
confidence: 99%